TINGKAT KRETIVITAS MAHASISWA DALAM BELAJAR AKUNTANSI KEUANGAN DITINJAU DARI MINAT BELAJAR - Sopiansah, Veri Aryanto (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
The aim of this research is to determine the differences in students' creative thinking abilities in the categories of high learning interest and low learning interest. The research method used is a comparative method with data analysis using the t test (one sample t-test) with ANOVA hypothesis testing. The participants in this research were students from the 2020 class of the economic education study program, Faculty of Teacher Training and Education, Pasundan University. This research was divided into two groups of students, namely the group of students in the high learning interest category and the students in the low learning interest category. interest. Based on the results of hypothesis testing, it is known that there are differences in the creative thinking abilities of students in the high learning interest category and students in the low learning interest category. Learning carried out by teachers must be able to pay attention to students' level of interest in learning because it will influence the learning process and outcomes, including thinking abilities, one of which is creative thinking.